Rafalskia azizsancari sp. n., a new harvestman (Opiliones: Phalangiidae) from Turkey - Kurt, Kemal; Yağmur, Ersen Aydın; Tezcan, Erman (Entomologica Fennica, 2019)
A new harvestman species, Rafalskia azizsancari sp. n., is described and illustrated based on male specimens collected from Bozdağlar Mountains, İzmir Province, Turkey. Most important differences between the new species and the three other species of the genus are included.